The Supervisor's Perceived Role in Employee Well-Being: Results From Mayo Clinic. Issue 2 (February 2019) - Wieneke, Kaisa C.; Schaepe, Karen S.; Egginton, Jason S.; Jenkins, Sarah M.; Block, Nicole C.; Riley, Beth A.; Sifuentes, Linde E.; Clark, Matthew M.
Purpose: Novel approaches are needed to enhance employee well-being and perhaps supervisors can be an effective agent for worksite health promotion. The aim of this study was to examine the supervisor's perceived needs, barriers, and role for influencing employee well-being for incorporation into program development. Design: Semistructured, qualitative interviews of supervisors. Setting: Large, integrated academic health-care organization with over 30 000 employees and 2600 supervisors having access to comprehensive well-being programs and a successful well-being champion network comprised of 600 champions. Participants: Twenty supervisors representing clinical, research, and administrative units. Methods: Semistructured, one-on-one interviews were conducted and audio recorded. Analysis included content log development and open coding by a trained analyst to reveal key themes. More formalized content coding using specialized software for qualitative analyses was also conducted. Results: Supervisor responses were wide ranging regarding their perceived and desired role in promoting workplace well-being. Barriers from the supervisor perspective included high current workload, ambivalence about promoting wellness, lack of support from leadership, lack of flexibility and control at work, and difficulty accessing on-site resources. They perceived their potential role in well-being as remaining a positive role model and encouraging their staff in wellness activities. Conclusion: Although findings are generated from a small sample size, these qualitative data provide compelling and early insights into building a workplace well-being strategy leveraging an underutilized key stakeholder, the workplace supervisor.